Diversity of Bactrocera spp. in Different Habitat Types in Citrus Orchards at Malang Regency - Rahmawati, Yunita Fera; Leksono, Amin Setyo; Gama, Zulfaidah Penata; Rizali, Akhmad (Al-Hayat: Journal of Biology and Applied Biology, 2024)
Fruit flies are important pests of citrus crops. Identifying fruit fly species is very important to make the appropriate conclusions in determining controlling methods. This study was intended to establish the dominant species, diversity index, and identification of fruit fly species in Siam citrus (Citrus nobilis Lour.) orchards in Dau District, Malang Regency, Indonesia. This study was conducted in two habitat types: close and far from residential areas. Six petrogenol-treated traps were placed at each location from December 2022 to February 2023, and every two weeks, the fruit flies caught in the traps were counted as part of the survey. The results showed that three species, namely B. dorsalis, B. carambolae, and B. umbrosa, were found in locations close to residential areas, while B. umbrosa was not found in locations far from residential areas. The dominant species was B. dorsalis in both locations. The diversity index of Bactrocera spp. in orchards close to residential areas was 1.14 (moderate), and Spearman's analysis (0.913) showed a more substantial influence than in orchards far from residential areas. Climatic factors of air humidity, air pressure, and host availability play an essential role in the presence of fruit flies.